The Routledge international handbook of public administration and digital governance - Giest, Sarah, 1986- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"The Routledge Handbook of Public Administration and Digital Governance is a comprehensive, cutting-edge guide for students, scholars and practitioners of public policy, public administration, and digital governance. The book demonstrates the diverse nature of "digital government" through a series of case studies from different regions across the globe, including Europe, Asia, Africa, and the Americas. The book uses these cases to highlight various aspects and implications of the intersection of digital technologies and public administration. These include impact of practices and principles of public administration, the effects of particular technologies/tools, and the relationship between state and citizen. The book also addresses barriers and enablers to the adoption of digital technology, with select chapters focusing on artificial intelligence in governmental contexts by leading practitioners and scholars. Rather than providing region-specific lessons, the cases identify common challenges, offering a more holistic understanding of public administration in the digital era. With contributions from both practitioners and scholars, this handbook will be a compelling resource for those researching, studying or working in in public administration, public leadership, information systems, and political science, and other related fields"--
Keywords: Political planning; Internet in public administration; BUSINESS & ECONOMICS / Government & Business; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / Comparative